Design and fabrication of humidity sensor. (2022) - Ikram, Mohd Mohsin; Ahmed, Farhan; Rizvi, S.J.A.
Abstract: Design and fabrication of the humidity sensor is done by using the different Degree of Sulfonation (DS) (15%, 29% and 42%) of the polymer Sulfonated-Poly ether ether ketone (sPEEK) which was derived by the sulfonation reaction using concentrated H2 SO4 with poly ether ether ketone (PEEK) and the reaction temperature was carried out in the microwave reactor. For different degree of sulfonation 2.0 wt% of nano powder of SiO2 (particle size 7 nm particle size 7 nm i.e. 0.007 µm purchased directly from Aldrich Chemistry Product Number: S5130) were added while dissolving the sPEEK beads of weight 1 g in DMSO solvent. Interdegitized copper electrode was etched on the conventional printed circuit board and the sensing area of 4.68 cm 2 . The polymer sPEEK is used as a sensing layer which shows the change in impedance as the relative humidity (%) increase as the impedance (ohm) value decreases vice versa and the impedance values was calculated by frequency response analyzer, auto lab potentiostat/galvanostat. The sensing nature of the sensing layer was measured at different thickness and at the different degree of sulfonation of the sPEEK. The sensor data was collected at different relative humidity chamber at 7%, 32%, 53%, 75% and 97% and all the data at different thickness of the sensing layer was linearized and important characteristics such as response time, recovery time, sensitivity and linearity were calculated.